A Survey of U.S. Education Policy Regarding the Education of Adults. Issue 5 (July 2020) - Roumell, Elizabeth Anne; Salajan, Florin D.; Todoran, Corina
In the United States, adult and workforce education (AE) seems to be located, simultaneously, both everywhere and nowhere in particular. Ongoing shifts in national economic demands and changes in requirements for training and education have brought learning in the adult years into the federal public policy arena. Sometimes referred to as lifelong learning, AE has proven to be a somewhat vague concept as a basis for federal policy formulation, but its existence signals an important federal locus of responsibility for learning in adulthood. This historical examination of the AE policy domain offers a review of the formulation, and more specifically how AE policy has been framed, where AE policy originated, and its progression over time. Primary U.S. legislative documents, federal agency reports, and federal white papers spanning the years 1862 to 2014 were reviewed to present a survey of the AE policy area.